EDUKASI PENGELOLAAN SAMPAH MELALUI PROGRAM SEDEKAH SAMPAH UNTUK PEMBUATAN PUPUK ORGANIK - Rita Zurina; Isnin Kurnia Safitri; Dwi Fitriani; Novitri Kurniati; Wismalinda Rita; Lezita Malianti (Jurnal Abdi Insani, 2026)
Household waste remains a major issue in Lubuk Unen Village, Merigi District, Bengkulu Province, due to population growth, residential development, and changes in consumption patterns that tend to produce more waste daily. Poorly managed household waste can have various negative impacts, such as soil, water, and air pollution, the emergence of unpleasant odors, clogged drainage channels, and increased risks of public health problems. Furthermore, waste accumulation can also reduce the quality of residential environments and the comfort of residents' lives. This situation demonstrates the importance of real efforts to raise public awareness in waste management from its source. This community service activity aims to increase community knowledge, awareness, and skills in waste management through the Sedekah Sampah program and the utilization of organic waste into valuable organic fertilizer. The Sedekah Sampah program is carried out by collecting inorganic waste that still has economic value to be sold, and the proceeds are used for the social benefit of the community. Meanwhile, organic waste such as food scraps, dry leaves, and kitchen waste is processed into organic fertilizer that can be used for yard plants and household-scale agricultural businesses. The program's implementation method involved socialization, outreach, training, hands-on practice, and participatory community mentoring. Results showed increased community understanding of the importance of waste sorting, increased community participation in the Sedekah Sampah (Trash Alms) program, and improved community skills in producing organic fertilizer from household waste. This program offers environmental, social, and economic benefits, thus potentially developing it as a model for community empowerment based on a circular economy and sustainable agriculture at the village level.